2017
DOI: 10.1097/qai.0000000000001541
|View full text |Cite
|
Sign up to set email alerts
|

HIV Transmission Dynamics Among Foreign-Born Persons in the United States

Abstract: Background In the United States (U.S.), foreign-born persons are disproportionately affected by HIV and differ epidemiologically from U.S.-born persons with diagnosed HIV infection. Understanding HIV transmission dynamics among foreign-born persons is important to guide HIV prevention efforts for these populations. We conducted molecular transmission network analysis to describe HIV transmission dynamics among foreign-born persons with diagnosed HIV. Methods Using HIV-1 polymerase nucleotide sequences report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Valverde et al's study, which focused on HIV transmission dynamics among US immigrants who were disproportionately affected by HIV, revealed that the majority of new HIV infections appeared subsequent to the immigration of related individuals to the USA. Consequently, the transmission network information regarding HIV acquirement and transmission routes among these individuals are required to improve HIV prevention among such populations [66]. In a phylodynamic study in South Africa using a large sequence dataset, the date of origin of 18 clades fell between 1979 and 1992 and a strong growth was found to have occurred in the 1990s.…”
Section: Molecular Network Monitor the Dynamics Of Local Hiv Transmimentioning
confidence: 99%
“…Valverde et al's study, which focused on HIV transmission dynamics among US immigrants who were disproportionately affected by HIV, revealed that the majority of new HIV infections appeared subsequent to the immigration of related individuals to the USA. Consequently, the transmission network information regarding HIV acquirement and transmission routes among these individuals are required to improve HIV prevention among such populations [66]. In a phylodynamic study in South Africa using a large sequence dataset, the date of origin of 18 clades fell between 1979 and 1992 and a strong growth was found to have occurred in the 1990s.…”
Section: Molecular Network Monitor the Dynamics Of Local Hiv Transmimentioning
confidence: 99%
“…In the United States (US), HIV/AIDS disproportionately affects Black/African American and Hispanic/Latino individuals, 1 notably Latino immigrants. 2 - 4 Of the more than 1.1 million Americans living with HIV/AIDS, 14% are unaware of their infection. 5 , 6 Undiagnosed HIV infections are an important public health concern, since those unknowingly infected serve as a reservoir for the ongoing transmission of HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Most originate from countries in South and East Asia, Latin America, sub‐Saharan Africa and the Caribbean and may therefore be considerably different in terms of socio‐cultural characteristics and health status compared with persons born in the US [2]. Studies in the US and Western Europe have suggested that the rate of HIV diagnosis may be higher among foreign‐born persons when compared with native‐born populations [3‐7]. For instance, adult HIV incidence rate in the Caribbean is second only to that in sub‐Saharan Africa [8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, adult HIV incidence rate in the Caribbean is second only to that in sub‐Saharan Africa [8]. These studies have also highlighted that foreign‐born persons both those who acquired HIV before and after migration have distinct epidemiologic profiles, including higher rates of diagnosis among women, lower rates of injection drug use transmission, higher rates of heterosexual transmission, higher CD4+ T cell counts at diagnosis and lower mortality rates [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation